Impact of clinical outcomes and imaging measures on health-related quality of life in secondary progressive MS. (July 2022) - W Koch, Marcus; Mostert, Jop; Repovic, Pavle; Bowen, James D; Strijbis, Eva; Uitdehaag, Bernard; Cutter, Gary
Background: Health-related quality of life (HRQOL) outcomes are often included as secondary outcomes in clinical trials in secondary progressive MS (SPMS), but little is known about the longitudinal association of HRQOL and clinical and imaging outcome measures in SPMS. Objective: To assess the association of change in clinical and imaging outcomes with HRQOL in people with SPMS. Methods: We used data from ASCEND, a large randomized controlled trial ( n = 889), to investigate the association of significant worsening on the Expanded Disability Status Scale (EDSS), Timed 25 Foot Walk (T25FW), Nine Hole Peg Test (NHPT), Symbol Digit Modalities Test (SDMT), and change in lesional and volumetric imaging outcomes with significant worsening on the 36-Item Short Form Health Survey (SF-36) and the Multiple Sclerosis Impact Scale (MSIS-29) during 2 years of follow-up using logistic regression models. Results: HRQOL measures were most associated with EDSS and T25FW, less so with NHPT and SDMT, and not associated with lesional and volumetric imaging outcomes. Discussion: Worsening of the EDSS and T25FW was associated with two commonly used HRQOL measures. These outcomes therefore appear to be more patient relevant than either the NHPT or SDMT in the context of a 2-year clinical trial.